The Influence of Work Discipline and Workload on Employee Performance: Study At One of The Banks in Bandung - Oktaviani, Nindi Dwi; Satria, Rd. Okky; Adinata, Ujang Wawan Sam; Sukmalana, Soelaiman; Supartini, Tini; Titi, Titi (Journal of Economics, Management, and Entrepreneurship, 2024)
This study was done by selecting a sample of 40 respondents from the population. This study investigates the use of SPSS 22 software for Windows operating systems. The research findings are as follows: A study was conducted to assess the work discipline of employees at a bank in Bandung. The data processing revealed that the average rating of respondents' responses was 2.98, which falls within the "Good enough" threshold. The workload of staff at a bank in Bandung was assessed by analyzing data processing results from respondents. The average score received was 3.00, which falls within the "Good enough" requirements for the test findings. The data processing findings from respondents at one of the banks in Bandung provided an overview of employee performance. The average score received was 3.28, which falls within the "Quite good" requirement for test results. The impact of work discipline and workload on employee performance at a bank in Bandung is as follows: the direct influence of work discipline on employee performance is 28.40%, and the indirect influence through work discipline is 17.44%. Therefore, the total influence of work discipline on employee performance is 46.95%. The impact of workload on employee performance at a bank in Bandung is directly influenced by work discipline, accounting for 17.44% of the total influence. Additionally, there is an indirect influence of 29.53% through workload, resulting in a total influence of work discipline on employee performance of 76.8% at this particular bank in Bandung. The impact of work discipline on employee performance at a bank in Bandung is measured at 0.546 or 54.6%, indicating a reasonably good correlation. Similarly, the influence of workload on employee performance at the same bank in Bandung is measured at 0.352 or 35.2%. The criteria are highly stringent, and the correlation between work discipline and workload is 0.892 or 89.2%, indicating a strong association. When considered jointly or concurrently, these factors have a combined total influence of 76.48%, with work discipline accounting for 46.95% and workload accounting for 29.53%. Hence, the overall impact amounts to 76.8%. The results indicate that the impact of these two variables falls within the very significant range, while the remaining elements, which have not been examined, also influence employee performance by 23.2%.